Distributed speed control for multi-three phase electrical motors with improved power sharing capability - Galassini, Alessandro; Costabeber, Alessando; Gerada, C.; Tessarolo, A. (2017)
This paper proposes a distributed speed control with improved power sharing capability for multi-three phase synchronous machines. This control technique allows the speed to be precisely regulated during power sharing transients among different drives. The proposed regulator is able to control the time constant of the current within the dq0 reference frame to a step input variation. If compared to current set-point step variations, the proposed droop controller minimises device’s stress, torque ripple, and thus mechanical vibrations. Furthermore, since distributed, it shows improved fault tolerance and reliability. The design procedure and the power sharing dynamic have been presented and analysed by means of Matlab/Simulink and validated in a 22kW experimental rig, showing good agreement with the expected performances.